Nano Lipid Carrier System Development for Dapagliflozin: Central Composite Design Approach - Vasam, Mallikarjun (Asian Journal of Pharmaceutics (AJP), 2024)
Original Research: The content involves original experimental work on the development of a nano lipid carrier system for Dapagliflozin using a central composite design approach. Methodology: It describes specific methodologies, such as the central composite design (CCD), and includes experimental data and results. Objective Analysis: The aim is to optimize a drug delivery system, which typically falls under the category of research articles in scientific journals.